Estabilização da tutela - Gonçalves, Eveline Berto (2020)
The purpose of this work is to analyze the institute of the stabilization of the guardianship from the principles that guide it, as it is used in the legal systems of Portugal and France, its emergence in Brazil and its regulation nor our legal system. Once the institute of guardianship stabilization has been standardized, the present work also presents how the operators of the law have been applying such instrument and whether, in fact, the possibility of stabilizing a guardianship has brought the long awaited speed and effectiveness. The rule in our country law is that of contradictory and broad defense, so that the institute should be applied in an exceptional manner, in cases where there is a need for an especially rapid judicial pronouncement, being indispensable the existence of a "contemporary urgency" to bring the action. There are still many gaps in the current law that make it difficult to understand and apply the stabilization of the tutelage and that will only be resolved over time, either through a new law or even through the understandings of the Higher Courts